Endoplasmic Reticulum Quality Control in Immune Cells - Jiang, Yalan; Tao, Zehua; Chen, Hua; Xia, Sheng (Frontiers in Cell and Developmental Biology, 2021)
The endoplasmic reticulum quality control (ERQC) system, including ER-associated degradation (ERAD), the unfolded protein response (UPR), and autophagy, presides over cellular protein secretion and maintains proteostasis in mammalian cells. As part of the immune system, a variety of proteins are synthesized and assembled correctly for the development, activation, and differentiation of immune cells, such as dendritic cells (DCs), macrophages, myeloid-derived-suppressor cells (MDSCs), lymphocytes, and natural killer (NK) cells. In this review, we emphasize the role of the ERQC in the production of these immune cells, and also discuss how the imbalance of ER homeostasis affects the immune response, thereby suggesting new therapeutic targets for immunotherapy.